A prospective study of novel mathematical analysis of the contrast-enhanced computed tomography vs renal scintigraphy in renal function evaluation. Issue 130 (September 2020) - Fiev, Dmitry; Proskura, Alexandra; Khokhlachev, Sergey; Taratkin, Mark; Borisov, Vladimir; Chernenkiy, Mikhail; Gabdulina, Svetlana; Leonard, Stephen Pax; Alyaev, Yuriy; Rivas, Juan Gomez; Enikeev, Dmitry; Glybochko, Petr
Highlights: Mathematical analysis of CT 3D models allows for precise renal function assessment. MACT allows to separately estimate function of right and left kidney. MACT could be done only if strict methodology of CT have been employed. Abstract: Purpose: whilst renal scintigraphy (RS) can be associated with interobserver variability, it remains the standard method of evaluating split renal function. Aim: to compare the efficacy of the novel technique of kidney function assessment and renal scintigraphy. Method: for this prospective single-arm study we recruited patients who were recommended dynamic renal scintigraphy with 99 mTc-DTPA (diethylenetriaminepentacetate). After scintigraphy, mathematical analysis of computed tomography (MACT) was done in all patients, by a single person (SK) blinded to RS results. Results: the study included a total of 97 patients with mean age of 50.9 (range, 23–78) years. From this sample, 65 were females and 32 males. All patients underwent both RS and contrast-enhanced computed tomography for further MACT in 2016−2018. CT results were found to be similar to renal scintigraphy results with Pearson correlation coefficient of 0.945 (р < 0.001). Substantial similarities in renal plasma flow for both kidneys were also observed (0.815, р < 0.001). Conclusion: MACT proved feasible, effective and safe in estimating renal function. Its results are closely correlated with RS findings and could be easily integrated into surgical practice.